Determining the Factors Fascinating Alumni towards Entrepreneurship: A Case Study of GCC - Mohammed Abdul Imran Khan (New Innovations in Economics, Business and Management Vol. 7, 2022)
Alumni entrepreneurship is a critical driver of economic growth. This research focuses on identifying factors that enhance entrepreneurial mindsets among Alumni in GCC (Gulf Cooperation Council). More specifically, the role of the government, entrepreneur incubators, entrepreneurial courses given at higher education institutions, and Alumni demographic factors in encouraging Alumni to embrace entrepreneurship must all be examined. This is a primary data-based study in which data was collected from a sample of 500 Alumni from GCC via a self-administered questionnaire and analysed using one-way ANOVA testing. The findings show that alumni entrepreneurs recognise the importance of the government, entrepreneurship courses, entrepreneur incubators, and demographic factors in encouraging them to pursue entrepreneurship. The study also aims to determine the impact of selected entrepreneurship course variables on GCC Alumni behaviours toward entrepreneurship. The government and the entrepreneurial course were shown to be the most influential factors in alumni’s decision to pursue entrepreneurship. Despite this, the low aggregate mean indicated that the majority of Alumni do not believe these bodies have performed satisfactorily. Whereas, according to the ANOVA results, age, academic level, and work experience were not significant determinants in motivating Alumni to pursue entrepreneurship. The level of unemployment among Alumni remains high throughout the region. The study’s final conclusion is that the government should play a more contemplative role in inspiring alumni to pursue entrepreneurship. The government should come up with more effective policies with ease in the procedures, laws and regulations for start-ups and existing businesses.